Analysis and applications of respiratory surface EMG: report of a round table meeting - Jonkman, A. H.; Warnaar, R. S.P.; Baccinelli, W.; Carbon, Niklas; D’Cruz, R. F.; Doorduin, J.; van Doorn, J. L.M.; Elshof, J.; Estrada-Petrocelli, L.; Graßhoff, J.; Heunks, L. M.A.; Koopman, A. A.; et al. (Critical Care, 2024)
Surface electromyography (sEMG) can be used to measure the electrical activity of the respiratory muscles. The possible applications of sEMG span from patients suffering from acute respiratory failure to patients receiving chronic home mechanical ventilation, to evaluate muscle function, titrate ventilatory support and guide treatment. However, sEMG is mainly used as a monitoring tool for research and its use in clinical practice is still limited—in part due to a lack of standardization and transparent reporting. During this round table meeting, recommendations on data acquisition, processing, interpretation, and potential clinical applications of respiratory sEMG were discussed. This paper informs the clinical researcher interested in respiratory muscle monitoring about the current state of the art on sEMG, knowledge gaps and potential future applications for patients with respiratory failure.
CRIS-Team Scopus Importer:2024-01-12